Analysis of Learning Outcomes of Buffer Solution Materials through the Discovery Learning Approach in Vocational High Schools - Ena, Trifiani A.B; Tangi, Hironimus C.; Lawung, Yustina D. (Universitas Pakuan, 2024)
This study aims to analyze the impact of the Discovery Learning approach on students’ learning outcomes in the topic of buffer solutions among Class XI science students at SMAK Sint Carolus Kupang, Indonesia. The research seeks to determine (1) the implementation of the Discovery Learning model in teaching buffer solution concepts, (2) students’ learning outcomes after applying the model, (3) student satisfaction with the Discovery Learning process, and (4) the effect and correlation between the use of Discovery Learning and student learning achievement. Using a descriptive-associative quantitative design, the study involved 30 students selected through purposive sampling. Data were collected through observation, achievement tests, and questionnaires, and analyzed using correlation and simple regression techniques. The results show that the implementation of Discovery Learning in chemistry lessons was categorized as good with a reliability rate of 98%, while the average learning outcome score reached 85, exceeding the school’s minimum completeness criteria of 75. Student satisfaction with the learning process was rated very good at 82%. Statistical analysis revealed a significant positive relationship between the Discovery Learning approach and learning outcomes, with a correlation coefficient of r = 0.40 and a regression equation of Y = 70.338 + 0.173X. These findings indicate that Discovery Learning fosters active student participation, enhances conceptual understanding of buffer solutions, and effectively improves chemistry learning outcomes.